Poczęcie naturalne, in vitro i „NaPro” - Gadzinowski, Janusz (Teologia i Moralność, 2018)
Infertility has been a big problem since the beginning of human existence. Some causes of infertility have always been present, other called ‟civilization causes” appeared recently, causing an increased need for treatment, hence the assisted reproductive technologies (ART), including “in-vitro”, have been introduced. Most children conceived with this method are healthy, but there is no doubt that it is a group of increased risk of various diseases. These methods are not accepted by the Catholic church, mainly because they involve killing or freezing of embryos regarded as human beings, but also for other reasons.